PENGARUH CORPORATE GOVERNANCE, PROFITABILITAS, DAN FINANCIAL LEVERAGE TERHADAP INCOME SMOOTHING (STUDI EMPIRIS PADA PERUSAHAAN YANG MASUK DALAM JAKARTA ISLAMIC INDEX) - Riski Kurniawan; Tertiarto Wahyudi; Kencana Dewi (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2016)
This study aims to determine the effect of corporate governance mechanism which proxied by institutional ownership, board of commissioners education background and audit committee meeting frequency as well as the effect of the profitability and financial leverage on the practice of smoothing profits (income smoothing). The study sample by 11 companies. This study used a methods quantitative approach and multiple regression data analysis using SPSS version 21. The results showed that in partial institutional ownership effect on positively to the practice of smoothing profits (income smoothing) while audit committee meeting frequency and profitability effect negative to the practice of smoothing profits (income smoothing) and board of commissioners education background and financial leverage has no effect to the practice of smoothing profits (income smoothing) on companies in the Jakarta Islamic Index. Simultaneously the institutional ownership, board of commissioners education background, audit committee meeting frequency , profitability, and financial leverage effect on the practice of smoothing profits (income smoothing) on companies in the Jakarta Islamic Index.